An unusual case of coronary artery compression that did not preclude successful transcatheter pulmonary valve placement. Issue 1 (16th April 2018) - Schwartz, Matthew C.; Felix, Donald; Iacono, Karen; Nykanen, David
Abstract: During transcatheter pulmonary valve placement, coronary compression observed during simultaneous right ventricular outflow tract angioplasty and coronary angiography typically contraindicates valve implantation. We present a unique patient with tetralogy of Fallot who underwent successful transcatheter Melody valve placement despite coronary compression observed during right ventricular outflow tract balloon angioplasty.